Characteristics of enhanced safety coordination between high-speed rail operators and manufacturers. (December 2021) - Bugalia, Nikhil; Maemura, Yu; Ozawa, Kazumasa
Highlights: Inter-organizational coordination for HSR rolling stock is important for safety. FRAM is used to model an incident and study inter-organizational complexity. Accidents can occur even when operators and manufacturers coordinate during design. Coordination should focus on micro-level integrated systematic risk-management. Moving beyond self-regulation, regulatory facilitation is necessary for solutions. Abstract: The current study analyzes safety issues that emerge owing to complex inter-organizational coordination between operators and manufacturers of high-speed railway (HSR) rolling stock, a topic rarely discussed in previous literature despite the prominence of HSR as an advanced transport mode. Risk factors pertinent to inter-organizational coordination between HSR stakeholders and solutions for managing these risk factors are critically examined through the functional resonance analysis method (FRAM) of an authentic safety incident. The analysis is conducted using official investigative reports and accounts of the incident triangulated from multiple sources within the Japanese HSR industry. Based on an FRAM-based taxonomical analysis of the theoretical solutions and considering the feasibility of the generated solutions, this study provides comprehensive and novel recommendations on the required characteristics of inter-organizational coordination for enhanced safety. In contrast to existing studies on safety coordination, the study finds that increased inter-organizational coordination between stakeholders directly involved in the process may not be sufficient to improve safety and that regulatory facilitation may be necessary. Moreover, the study concludes that the necessary coordination between stakeholders across the safety management process should be structured in order to conduct industry-wide integrated systematic risk assessments.